Trade in Northeast Asia: why do trade costs matter? - Prabir De (Center for Economic Studies and ifo Institute (CESifo), 2006)
Trade costs are often cited as an important determinant of the volume of trade. This paper provides enough evidences to ascertain that today's trade issues in Northeast Asia go beyond the traditional mechanisms of tariffs, and include behind-the-border issues. By estimating a modified gravity equation, controlling for endogeneity and remoteness, we find that variations in transaction costs along with trade infrastructure facilities have significant influence on regional trade flows in Northeast Asia. On average, 10 percent saving in transaction costs increases imports by about 5 percent in Northeast Asia. This paper concludes that when tariffs tend to become low in Northeast Asia, the economies in this region could potentially benefit substantially from higher trade provided trade costs are well controlled.
Keywords: F02; F10; F15; 330; Außenwirtschaft; Transaktionskosten; Außenhandelsbeschränkung; Nichttarifäre Handelshemmnisse; Asien (Nordost)